Effects of filtermud on growth and yield of three banana cultivars grown in Kenana Sugar Scheme area, central Sudan - Mahmoud, Haroun I.; Elkashif, Mohamed E.; F.E.Widaa, Abu elgasim (Gezira Journal of Agricultural Science; Vol 14 No 2 (2016), 2016)
ABSTRACT  Banana is an important fruit crop in the Sudan and its production is mainly confined to the alluvial deposits of rivers. Organic matter is known to improve soil physical and chemical characteristics and provide plant mineral nutrients. Therefore, the objective of this research was to evaluate the effects of filtermud levels on vegetative growth, yield components and total yield of the mother, first, second and third ratoon crops of three banana cultivars. Field experiments were conducted during December 2012 to November 2014 at Kenana Sugar Scheme area. Banana cultivars were the introduced banana clones Williams Hybrid and Grand Nain and the local cultivar Dwarf Cavendish. Levels of filtermud were 15% and 30% by volume. Treatments were arranged in a randomized complete block design with four replicates. Three months after planting, two plants from each plot were randomly selected, tagged and used for growth and yield measurements. Results showed significant differences among cultivars in vegetative growth, yield components and total yield. The introduced banana clones Williams Hybrid and Grand Nain had the most vigorous vegetative growth and the highest yield components and total yield compared to that of the local cultivar Dwarf Cavendish. However, Dwarf Cavendish was earlier than the introduced clones. Application of filtermud at both rates resulted in a significant increase in all vegetative growth parameters and in the earliness of banana crop. Filtermud also produced a significant increase in all yield components and total yield compared to the untreated control. It is recommended to grow the introduced cultivars Williams Hybrid and Grand Nain and apply filtermud at the rate of 15% by volume in heavy clay soils.